ANALISIS FAKTOR-FAKTOR PERCAYA DIRI PESERTA DIDIK - Yeyen Tri Kusumaningsih; Heri Saptadi Ismanto (Universitas Muhammadiyah Metro, 2024)
The aim of this research is to determine the self-confidence factors of class X students at SMA Negeri 8 Semarang. The data collection method in this research uses a qualitative approach whose instruments consist of interviews and observations. From the results of data analysis, it was concluded that there are several self confidence factors which are categorized as low self-confidence, namely 1.) physical factors, students feel they have shortcomings. 2). mental factors, 5 students do not dare to express opinions either at school or in their environment, assess themselves as less capable in doing things, feel inferior when in front of friends, 3). Social factors: The student does not have many friends, prefers to be alone and is not good at socializing. From the results of the research, the results of a case study of 5 participants at SMA Negeri 8 Semarang explained that the 5 students and girls of class X tend to have low self-confidence. mental assessment, the subject in class does not dare to express an opinion, does not want to come to the front of the class, never shows his school work to his friends, if he has difficulty in class assignments, the subject does not dare to ask his teacher, usually asks his close friends , social assessment, self-confidence can be influenced by environmental factors as well.